Approximate stabilization for a nonlinear parabolic boundary-value problem - Kapustyan, O. A.; Kapustyan, O. V.; Sukretna, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
For a problem of optimal stabilization of solutions of a nonlinear parabolic boundary-value problem with small parameter of a nonlinear summand, we justify the form of approximate regulator on the basis of the formula of optimal synthesis of the corresponding linear quadratic problem.